Treatment with a proton pump inhibitor improves glycaemic control in type 2 diabetic patients. - Saha, Shusmita; Chowdhury, Achinta N (Journal of Dhaka National Medical College & Hospital, 2022)
Oral hypoglycemic medications sometimes do not control type 2 diabetes well. Proton pump inhibitors as adjunctive therapy might improve diabetes control through increasing serum gastrin & fasting insulin levels. Proton pump inhibitor therapy also associated with lower glycosylated hemoglobin levels in diabetes J. Dhaka National Med. Coll. Hos. 2022; 28 (01): 42-45